Pengaruh Konservatisme Akuntansi dan Mekanisme Corporate Governance Terhadap Penghindaran Pajak - Gita Gustiani Erawadi; Dadan Soekardan (Jurnal Riset Mahasiswa, 2021)
This study aims to determine the magnitude of the influence of Accounting Conservatism and Corporate Governance Mechanisms (Institutional Ownership, Managerial Ownership, Independent Board of Commissioners, Audit Quality and Audit Committee) on Tax Avoidance. The unit of analysis used in this study is a plantation company listed on the Indonesia Stock Exchange in the period 2014-2018. The method used in this research is descriptive and associative method. This study uses secondary data in the form of annual financial reports and annual reports obtained from the company's official website. The sampling technique used in this research is purposive sampling. In this study a population of 18 companies and a sample of 11 companies listed on the Indonesia Stock Exchange. The results of this study indicate that accounting conservatism has no significant effect on tax avoidance. Institutional Ownership has no significant effect on Tax Avoidance. Managerial Ownership has no significant effect on Tax Avoidance. The Board of Independent Commissioners has a significant effect on Tax Avoidance. Audit Quality has no significant effect on Tax Avoidance. The Audit Committee has a significant effect on Tax Avoidance. Corporate Governance Mechanism.